Pengaruh Kualitas Produk Dan Inovasi Produk Terhadap Kepuasan Konsumen Produk Ms Glow Dengan Kepercayaan Sebagai Variabel Intervening: Studi Kasus Pada Mahasiswa STIE Bina Karya Tebing Tinggi - Siregar, Aisyah; Ningsih, Erna (Management And Business Progress, 2023)
This study aims to examine and determine the effect of Product Quality and Product Innovation on Consumer Satisfaction of MS Glow products with Trust as an Intervening Variable. The effect we want to know is the direct or indirect effect. This type of research is explanatory research that describes the location of the variables studied and their effects from one variable to another. The population in this study is unknown in number. The sample taken was 96 respondents using the Cochran formula with proportionate stratified random sampling technique with the characteristics of STIE Bina Karya students in semester 2, 4, 6 & 8, aged at least 18 years and had used MS Glow products for at least 3 months. The data analysis method uses PLS-based SEM, analyzed by outer model, inner model and hypothesis testing using bootstrapping. The results of this study indicate that Product Quality has a positive and significant effect on Trust. Product Innovation has a positive and significant effect on Trust. Product Quality has a positive and significant effect on Consumer Satisfaction. Product Innovation has a positive and significant effect on Consumer Satisfaction. Trust has a positive and significant effect on Consumer Satisfaction. Product Quality has a positive and significant effect on Consumer Satisfaction through Trust as an Intervening Variable. Product Innovation has a positive and significant effect on Consumer Satisfaction through Trust as an Intervening Variable.